Performance of a Horizontal Triple Cylinder Type Pulping Machine - Sukrisno Widyotomo; H. Ahmad; S.T. Soekarno; Sri Mulato (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2011)
Pulping is one important step in wet coffee processing method. Pulping process usually uses a machine which constructed by wood or metal materials. A horizontal single cylinder type of fresh coffee cherries pulping machine is the most popular machine in coffee processing. One of the weaknesses of a horizontal single cylinder type of fresh coffee cherries pulping machine is higher in broken beans. Broken bean is one of mayor aspects in defect system that contribute to low quality. Indonesian Coffee and Cocoa Research Institute has designed and tested a horizontal double cylinder type of fresh coffee cherries pulping machine which resulted in 12.6—21.4% of broken beans. To reduce percentage of broken beans, Indonesian Coffee and Cocoa Research Institute has developed and tested a horizontal triple cylinder type of fresh coffee cherries pulping machine. Material tested was fresh mature Robusta coffee cherries, 60—65% (wet basis) moisture content; has classified on 3 levels i.e. unsorted, small and medium, and clean from metal and foreign materials. The result showed that the machine produced 6,340 kg/h in optimal capacity for operational conditions, 1400 rpm rotor rotation speed for unsorted coffee cherries with composition 55.5% whole parchment coffee, 3.66% broken beans, and 1% beans in wet skin.Key words : coffee, pulp, pulper, cylinder, quality.